The Existence of Hadith as a Moral Compass for the Life of Teenagers in the Digital Era: A Study of the Hadith of the Book of Riyadhussholihin - Euis Supianah; Romlah Abu Bakar Askar; Munzir Suparta (Penerbit Hellow Pustaka, 2025)
The rapid development of the digital era has significantly influenced the lives of adolescents, particularly in their mindset, behavior, and moral values. The vast and fast-paced access to information is often not accompanied by adequate critical filtering skills, which can lead to moral crises and a loss of direction. In this context, the hadiths of the Prophet Muhammad SAW, compiled in Riyaadhussholihin by Imam Nawawi, serve as a relevant moral compass for today's youth. This study aims to examine the role of the hadiths in Riyaadhussholihin as a guide for moral direction in facing the challenges of the digital age. Utilizing a library research method with a descriptive-qualitative approach, this study finds that the content of the hadiths in the collection contains noble values such as honesty, responsibility, simplicity, restraint of speech and actions from negative behavior, and self-control. These values are crucial to instill in the younger generation to help shape a strong, ethical, and wise character capable of navigating the currents of globalization and digitalization. Character education based on hadiths emerges as an alternative solution to strengthen the moral identity of Muslim youth today.